2009
DOI: 10.1590/s0004-282x2009000200022
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar cryptococcoma simulating metastatic neoplasm

Abstract: Neurocryptococcosis is a common mycotic central nervous system infection caused by the neurotropic fungus Cryptococcus neoformans 1 . It is most frequently found as the pathological presentation of cryptococcal meningoencephalitis 1 . Other rare forms of central nervous system cryptococcal infections are their solid-granulomatous appearance and abscesses, both being commonly named neurocryptococcomas, because of the mass effect they cause in surrounding tissue and their "tumoral aspect", many times simulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Most were in immunocompetent patients, chronic and progressive headache associated with nausea and vomiting was the main symptom during the onset of the disease. One case had cerebellar symptoms such as ataxia and dysdiadochokinesia 9 ; in another case the alteration of the state of consciousness was one of the first symptoms 10 , and in another no meningeal signs were reported 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most were in immunocompetent patients, chronic and progressive headache associated with nausea and vomiting was the main symptom during the onset of the disease. One case had cerebellar symptoms such as ataxia and dysdiadochokinesia 9 ; in another case the alteration of the state of consciousness was one of the first symptoms 10 , and in another no meningeal signs were reported 11 .…”
Section: Discussionmentioning
confidence: 99%
“…La mayoría se presentaron en pacientes inmunocompetentes, la cefalea crónica y progresiva asociada a nausea y vómito, fue el principal síntoma durante el debut de la enfermedad. Un caso presentó síntomas cerebelosos como ataxia y disdiadococinesia 9 ; en otro caso la alteración del estado de conciencia fue uno de los primeros síntomas 10 y en otro tampoco se reportaron signos meníngeos 11 .…”
Section: Discussionunclassified
“…A review of the literature revealed only 5 reported cases. 3,4,6,12,13 Data regarding these cases are summarized in Table 1. Only 1 case reported by Kanaly et al 4 had a pulmonary lesion that was caused by sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…2 CNS cryptococcoma is a rare condition affecting the cerebral hemispheres or cerebellum. 3,4 It is secondary to infectious spread along the perivascular spaces (Virchow-Robins [VR] spaces) into the brain parenchyma. This fungus typically colonises the VR spaces.…”
Section: Discussionmentioning
confidence: 99%